The Effects of Climate Change on Human Behavior and Stress - Mitra Sadat Fathifard; Fateme Javid; Abbas Rahdan (اکولوژی انسانی, 2023)
Climate change has become a global, cross-cultural challenge, significantly impacting human lives. The phenomenon has led to an increase in surface temperature, sudden weather events, and alterations in precipitation patterns. These changes pose new challenges in public health, food safety, and economic stability across various regions. This research, characterized as a descriptive-analytical study with an emphasis on quantitative methods, aims to assess physiological stress for the establishment of comfort in heat absorption and dissipation (Case study: Gilan Province). The objective is to identify high and low physiological stress levels above 20 degrees and below 20 degrees Celsius, respectively. Criteria such as air temperature in Fahrenheit, average relative humidity, minimum air temperature, and wind speed were considered for the evaluation. The data from meteorological stations in Gilan Province were used to classify the physiological stress index, and the final output was calculated using the Heat Comfort Coefficient in GIS environment. All processes and data analysis in GIS environment were assessed using the Inverse Distance Weighting (IDW) statistical model, which predicts the spatial structure of unknown points based on the correlation between measured points. In the end, the final output map was categorized into 7 separate layers for both temperature ranges. The results of the physiological stress assessment indicated that most days in the central parts of Gilan Province are associated with comfort in heat absorption and dissipation, promoting human health.